A nanofluid for selectively blocking gas channel and its preparation method and application
By using a nanofluid system composed of modified nanoparticles and activators, gels are formed and dehydrated under the action of gas to form glass-like solid substances, the problem of difficult gas trajectory in gas injection development in low-permeability reservoirs is solved, and the effect of selective sealing and improving reservoir recovery is achieved.
Patent Information
- Application Number
- CN202311083381.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-28
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-08-28
AI Technical Summary
Low permeability oil reservoirs are prone to gas traversal during gas injection development, resulting in a drop in volume and difficulty in producing residual oil, and it is difficult for the prior art to selectively block gas traversal channels.
A nanofluid system is adopted, which consists of modified nano SiO2 or nano TiO2 particles, activators, dispersants and clay stabilizers, forms gels through covalent bonds, and dehydrates under the action of gas to form glass-like solid substances, reducing gas-phase permeability to achieve selective sealing.
This nanofluid system has good injection properties and sealing effect, can selectively seal gas traversal, improve reservoir recovery, and has less damage to the oil phase and the water phase.
Smart Images

Figure BDA0004415387340000041 
Figure BDA0004415387340000042 
Figure BDA0004415387340000051
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oilfield chemistry, in particular to a selective profile control and water plugging technology for oil reservoirs, and specifically to a nanofluid for selectively plugging gas channeling channels, and a preparation method and application thereof. Background Art
[0002] After conventional water injection development of the reservoir, the block as a whole enters a high water content stage, the injected water flows along the fractures, the water flooding is serious, the overall oil recovery efficiency is low, the stable production time is short, and the development effect is poor. Among them, gas injection development has a strong injection capacity, the gas can penetrate into smaller pores and displace more crude oil, so gas injection is one of the most popular EOR technologies at present. However, low permeability reservoirs usually have strong heterogeneity, which will produce an unfavorable mobility ratio during the gas injection process, and it is very easy to form gas channeling, resulting in a decrease in the swept volume, and a large amount of residual oil cannot be produced in time. Therefore, whether the gas channeling can be successfully delayed and suppressed is the key to the success of air injection development of low permeability reservoirs.
[0003] At present, the means of controlling gas channeling can be summarized as "injection-production coordination, water-gas alternation, and chemical sealing". Adjusting the well network and changing the injection parameters are the most basic control measures, but this method is only applicable to blocks with weak heterogeneity and less gas channeling. When the geological conditions are harsh, the sealing effect that can be achieved is extremely limited. Water-gas alternation is simple to operate, highly economical, and harmless to the reservoir. It introduces another phase of fluid to change the relative permeability of the gas, increase the viscosity of the injected air, improve the mobility ratio, and thus reduce channeling. It is a widely used control measure. However, this method has a poor effect on reservoirs with large permeability differences and large cracks. At the same time, a high water-gas ratio means a relatively reduced gas injection volume, and the oil recovery effect will be greatly affected. The main principle of using chemical reagents to seal the formation is to block the local high permeability area to achieve relative homogeneity of the heterogeneous reservoir, which is the most effective means of deep profile adjustment. Polymers, gels and foams are the main research directions of current chemical plugging technology. They have good plugging effects and can effectively improve the sweep coefficient of the reservoir. However, these technologies cannot selectively plug gas channel channels and may damage the oil layer.
[0004] Considering the selective plugging of gas channeling, domestic and foreign scholars have focused on the research of systems for selective plugging of gas channeling, but there are few related studies. Wang and Zhang used n-butylamine as a plugging agent to plug the gas channeling and found that the CO2 concentration in the gas channeling with high permeability was high, which was the main space for the reaction with amines. The solid products generated would effectively block the channel, while for the matrix area with low permeability, CO2 was difficult to spread and difficult to react with amines, so it was selective. However, the organic amines currently used are biologically toxic and have a great impact on the environment, which limits their large-scale application in mines. Jia Hu analyzed the mechanism of action of polymer gel under pressure from gas and salt water, and found that the microscopic seepage ability of water in the gel was stronger than that of gas, while the microscopic seepage ability of gas in the porous medium after gel plugging was poor. Therefore, the gas channeling channel can be selectively blocked by injecting polymer gel. Zheng Peng used a "one-step method" to synthesize a heat / CO2 dual-stimulation viscosity-increasing polymer, and found that when the concentration was higher than 0.1wt%, the polymer aqueous solution showed good heat and CO2-stimulated viscosity-increasing ability; when the temperature was lowered or N2 was introduced to expel the CO2 in the system, the system viscosity could return to the initial state, and after multiple cycles, it still showed good viscosity "switch" responsiveness. At present, the research on selective blocking of gas channel is still in the initial exploration stage, so it is urgent to develop a gas channel blocking system that can selectively block gas channel and has good injectability and blocking properties. Summary of the invention
[0005] In order to solve at least one of the above problems, an object of the present invention is to provide a nanofluid for selectively blocking gas channeling, wherein the raw materials thereof are composed as follows by mass content:
[0006] Nanoparticles: 30% to 32%,
[0007] Activator: 20-22%,
[0008] Dispersant: 0.1%~0.2%,
[0009] Clay stabilizer: 0.1%~0.2%,
[0010] The rest is water;
[0011] The sum of the above components is 100%.
[0012] In the present invention, the nanoparticles are one of nano-SiO2 particles and nano-TiO2 particles whose surfaces are modified by a silane coupling agent, wherein the mass ratio of nanoparticles: solvent: silane coupling agent in the nanoparticle modification process is: 1: (9-11): (2-5); the solvent is one of toluene, ethylene glycol, and ethanol; the silane coupling agent is one of silane coupling agent KH550 and silane coupling agent KH560; the activator is sodium silicate (NaSil); the dispersant is one of sodium dodecylbenzenesulfonate (SDBS), hexadecyltrimethylammonium bromide (CTAB), and Triton X-100 (TX-100); and the clay stabilizer is one of sodium hydroxide (NaOH) and potassium hydroxide (KOH).
[0013] The present invention also provides a method for preparing a nanofluid system for selectively blocking gas channeling, which is used to prepare the above nanofluid system. The specific preparation steps are as follows:
[0014] (1) drying the nanoparticles to obtain pretreated activated nanoparticles; adding the pretreated activated nanoparticles and the coupling agent to a solvent under stirring conditions, stirring and reacting at 75 to 90° C., and then filtering and drying to obtain modified nanoparticles; in this step, the drying conditions can be freely selected, such as drying in a vacuum drying oven at 90 to 110° C. for 24 hours, or drying at normal pressure.
[0015] (2) gradually adding the modified nanoparticles into fresh water under stirring conditions to obtain a modified nanoparticle suspension.
[0016] (3) Adding a dispersant and a clay stabilizer to the modified nanoparticle suspension prepared in step (2) in sequence, keeping the pH value of the solution at 10 to 11, stirring evenly, so that the dispersant and the clay stabilizer can be well dissolved in the nanoparticle dispersion system, and obtaining a nanoparticle water-based solution system.
[0017] (4) adding an activator to the nanoparticle water-based solution system formed in step (3) under stirring conditions and stirring sufficiently to form a nanofluid system.
[0018] Another object of the present invention is to provide an application method of the above-mentioned nanofluid system for selectively plugging gas channel, wherein the nanofluid system prepared in step (4) is injected into the formation, a covalent bond is formed between the nanoparticles and the activator, a gel begins to form, and a gas containing CO2 is added to the formation so that the CO2 passes through the gel and is dehydrated to form a glassy solid substance, thereby reducing the gas permeability and achieving the plugging of the gas production channel.
[0019] Under the combined effect of the above steps, selective gas blocking of gas-broadcasting oil wells can be achieved, thereby improving the oil reservoir recovery rate.
[0020] In summary, the present invention has the following advantages:
[0021] (1) The nanofluid system prepared by the present invention has low viscosity and good injectability.
[0022] (2) After the nanofluid system prepared by the present invention is injected into the formation, it is dehydrated under the action of gas to form a glassy solid substance, thereby reducing the relative permeability of the gas phase and effectively blocking the gas channel.
[0023] (3) The nanofluid system prepared by the present invention forms an unstable gel in a high oil saturation formation, which has little damage to the oil phase and the water phase. However, the glassy solid substance formed under the action of gas has a greater impact on the gas phase and has the characteristic of selectively blocking gas but not oil. DETAILED DESCRIPTION
[0024] The specific implementation modes of the present invention will be described clearly and completely below with reference to examples. Obviously, the examples described are only some embodiments of the present invention, rather than all embodiments.
[0025] Unless otherwise specified, the percentages in this embodiment are all by mass.
[0026] The present invention will be further described below in conjunction with embodiments:
[0027] The specific implementation modes of the present invention will be described clearly and completely below with reference to examples. Obviously, the examples described are only some embodiments of the present invention, rather than all embodiments.
[0028] In the following embodiments, unless otherwise specified, the operations described are routine operations in the art.
[0029] In the following examples, unless otherwise specified, the raw materials used can be obtained through conventional commercial channels.
[0030] Example 1
[0031] In this embodiment, the specific steps of the nanofluid system are as follows:
[0032] (1) Dry 50 g of nano-SiO2 particles in a vacuum drying oven at 100°C for 24 h, and after naturally cooling to room temperature, obtain pretreated activated nanoparticles; add the pretreated activated nanoparticles and 150 g of silane coupling agent KH550 into 500 g of toluene solvent under high-speed stirring, stir at 80°C for 2 h, and then filter and dry at a high temperature of 200°C for 2 h to obtain modified nanoparticles.
[0033] (2) Take 32 g of the modified nano-SiO2 particles prepared in step (1) and add them to 48 mL of fresh water. Mechanically stir at high speed for 12 h to suspend the nano-SiO2 particles in the aqueous solution to form a modified nano-SiO2 suspension.
[0034] (3) 0.15 g of sodium dodecylbenzenesulfonate (SDBS) and 0.15 g of 1 mol / L potassium hydroxide were added to the modified nano-SiO2 suspension prepared in step (2) (the pH value of the solution was 10) in sequence, and after mechanical stirring for 30 min, the suspension was transferred to an ultrasonic disperser and heated to 60°C. After several hours of sonication, a clear modified nano-SiO2 water-based solution was obtained.
[0035] (4) Add 20 g of sodium silicate into the nano-SiO2 water-based solution and mechanically stir for 1 hour to form a nanofluid system.
[0036] Performance Testing
[0037] 1. Gelation time
[0038] The nanofluid in this embodiment was heated in a constant temperature forced air drying oven at 90°C, and the viscosity of the nanofluid at the initial moment was measured using a Brookfield DV-III rotational viscometer. The viscosity was also measured after 2h, 4h, 8h, 12h, 24h, 36h, 48h, and 60h of reaction. The test results are shown in Table 1.
[0039] Table 1 Relationship between gelation time and viscosity of nanofluids
[0040]
[0041] The above viscosity test results show that the initial viscosity of the nanofluid system of this embodiment is relatively small when the configuration is completed, which is close to the viscosity of water, indicating that it has good injectability; the nanofluid system of this embodiment has a high temperature of 90°C, and the gelling viscosity increases sharply with the increase of injection time, and the viscosity is the largest at 48h, indicating that the nanofluid system of this embodiment has a gelling time of 48h at a high temperature of 90°C. After 48h, the nanofluid system of this embodiment began to decline to a certain extent, indicating that it has degraded to a certain extent, but it can still maintain a high viscosity, indicating that the nanofluid system of this embodiment has sufficient plugging ability.
[0042] 2. Gel strength
[0043] The nanofluid system of this embodiment was taken, and its gel strength after 48 hours of reaction was measured according to the gel strength visual code standard table in Table 2, and the gel strength of the system was found to be D grade.
[0044] Table 2 Gel strength visual code standard table
[0045]
[0046]
[0047] 3. Stability
[0048] The nanofluid of this embodiment was placed in a constant temperature blast drying oven at 90° C. for aging. After gelation, the gelation was observed at regular intervals. The viscosity of the nanofluid at the initial moment was measured using a Brookfield DV-III rotational viscometer. The test results are shown in Table 3.
[0049] Table 3 Relationship between nanofluid aging time and viscosity
[0050] Gelation time / d 0 1 2 5 10 15 30 60 Viscosity / mPa·s 2.5 402.5 1510.2 1240.6 985.3 767.9 499.2 385.3
[0051] The above viscosity test results show that as the aging time increases, the viscosity of the system gradually decreases.
[0052] 4. Sealing performance
[0053] The core was evacuated and saturated with formation water, the core pore volume was calculated, and the core permeability was measured with water; the core was saturated with oil and the oil phase permeability was measured; CO2 was injected to saturate the core and the initial gas phase permeability was measured; the core was taken out, fractured and cracked, and the crack width was controlled by filling with sand; the core was put back into the core holder and CO2 was displaced until gas channeling (continuous gas production at the core outlet and no oil was produced), and the gas drive was stopped; 0.7FV of the nanofluid system of this embodiment was injected; after aging in a 90°C thermostat for 72h, CO2 was injected for secondary gas drive to investigate the sealing effect of the system in sealing cracks. The test results are shown in Table 3.
[0054] Table 4 Changes in three-phase permeability before and after injection into the system
[0055] <![CDATA[Permeability before injection system / 10 -3 μm 2 > <![CDATA[Permeability after injection into the system / 10 -3 μm 2 > Blockage rate / % Gas Phase 32 1.5 95.3 oil phase 12.8 12.1 5.4 Water Phase 19.2 7.2 62.5
[0056] The above table shows that the system can significantly reduce the permeability of the gas phase, has a general effect on the permeability reduction of the water phase, and has little effect on the permeability of the oil phase. Therefore, it has a stronger plugging property for the gas phase and a weaker plugging property for the oil phase, and can achieve selective plugging of the gas phase. The principle is: because the activator is cationic, it interacts with the anionic modified nanoparticles to reduce the repulsive force between the modified nanoparticles. A covalent bond (siloxane bond O-Si-O) is formed between the modified nanoparticles and the activator, and they collide and adhere to each other through covalent bonds, and begin to cross-link to form a gel. When gas is not injected, in the anti-rhythmic low-permeability reservoir, the permeability of the upper reservoir is greater than that of the lower reservoir, and the oil saturation of the two reservoirs is the same. When gas is injected, a large number of alkaline adsorption sites are formed on the surface of the gel formed by the modified nanofluid, and chemical adsorption of acid-base reaction occurs, which improves the gel's ability to adsorb CO2. The gas flows along the upper high permeability layer to form a gas channel, pushing the residual oil in the pores to the oil well, while the gas in the lower part of the reservoir is not affected, and this part of the residual oil is not produced. Therefore, the oil saturation of the lower reservoir is greater than that of the upper reservoir. After the nanofluid system is injected, the gel formed forms a glassy solid substance under the action of the gas. The solid substance has a greater impact on the gas phase permeability. However, due to the high oil saturation of the lower reservoir, the formed gel is unstable and does not cause much damage to the oil phase and water phase of the lower reservoir. Therefore, after the nanofluid system is injected, the gas channel is blocked at the gas injection end, and the residual oil in the lower reservoir is displaced after gas injection, thereby improving the oil recovery rate of the reservoir.
[0057] Example 2
[0058] In this embodiment, the specific steps of the nanofluid system are as follows:
[0059] (1) Dry 50 g of nano-TiO2 particles in a vacuum drying oven at 100°C for 24 h, and after naturally cooling to room temperature, obtain pretreated activated nano-particles; add the pretreated activated nano-particles and 100 g of silane coupling agent KH560 into 450 g of ethylene glycol solvent under high-speed stirring, stir at 75°C for 2 h, and then filter and dry at a high temperature of 200°C for 2 h to obtain modified nano-TiO2 particles.
[0060] (2) Take 30 g of the modified nano-TiO2 particles prepared in step (1) and add them to 48 mL of fresh water. Mechanically stir at high speed for 12 h to suspend the nano-TiO2 particles in the aqueous solution to form a modified nano-TiO2 suspension.
[0061] (3) 0.1 g of Triton (TX-100) and 0.2 g of 1 mol / L sodium hydroxide were added to the modified nano-TiO2 suspension prepared in step (2) (the pH value of the solution was 11) in sequence, and after mechanical stirring for 30 min, the suspension was transferred to an ultrasonic disperser and heated to 60°C. After several hours of sonication, a clear modified nano-TiO2 water-based solution was obtained, and its viscosity was equivalent to that of water.
[0062] (4) Add 22 g of sodium silicate into the aqueous solution of nano-TiO2 and stir mechanically for 1 h to form a nanofluid system.
[0063] Performance Testing
[0064] 1. Gelation time
[0065] The nanofluid in this embodiment was heated in a constant temperature forced air drying oven at 90°C, and the viscosity of the nanofluid at the initial moment was measured using a Brookfield DV-III rotational viscometer. The viscosity was also measured after 2h, 4h, 8h, 12h, 24h, 36h, 48h, and 60h of reaction. The test results are shown in Table 5.
[0066] Table 5 Relationship between gelation time and viscosity of nanofluids
[0067] Gelation time / h 0 4 8 12 24 36 48 60 Viscosity / mPa·s 1.8 13.2 39.5 98.9 387.5 965.5 1480.2 1396.4
[0068] The above viscosity test results show that the initial viscosity of the nanofluid system of this embodiment is relatively small when the configuration is completed, which is close to the viscosity of water, indicating that it has good injectability; the nanofluid system of this embodiment has a high temperature of 90°C, and the gelling viscosity increases sharply with the increase of injection time, and the viscosity is the largest at 48h, indicating that the nanofluid system of this embodiment has a gelling time of 48h at a high temperature of 90°C. After 48h, the nanofluid system of this embodiment began to decline to a certain extent, indicating that it has degraded to a certain extent, but it can still maintain a high viscosity, indicating that the nanofluid system of this embodiment has sufficient plugging ability.
[0069] 2. Gel strength
[0070] The nanofluid system of this embodiment was taken, and its gel strength after 48 hours of reaction was measured according to the gel strength visual code standard table in Table 2, and the gel strength of the system was found to be D grade.
[0071] 3. Stability
[0072] The nanofluid in the embodiment was placed in a constant temperature blast drying oven at 90°C for aging. After gelation, the gelation was observed at regular intervals. The viscosity of the nanofluid at the initial moment was measured using a Brookfield DV-III rotational viscometer. The test results are shown in Table 6.
[0073] Table 6 Relationship between nanofluid aging time and viscosity
[0074] Gelation time / d 0 1 2 5 10 15 30 60 Viscosity / mPa·s 2.5 387.5 1480.2 1164.3 897.4 702.7 473.7 310.2
[0075] The above viscosity test results show that as the aging time increases, the viscosity of the system gradually decreases.
[0076] 4. Sealing performance
[0077] The core was evacuated and saturated with formation water, the core pore volume was calculated, and the core permeability was measured with water; the core was saturated with oil and the oil phase permeability was measured; CO2 was injected to saturate the core and the initial gas phase permeability was measured; the core was taken out, fractured and cracked, and the crack width was controlled by sand filling; the core was put back into the core holder and CO2 was displaced until gas channeling (continuous gas production at the core outlet and no oil was produced), and the gas drive was stopped; 0.7FV of the nanofluid system of this embodiment was injected; after aging in a 90°C thermostat for 72h, CO2 was injected for secondary gas drive to investigate the sealing effect of the system in sealing cracks. The test results are shown in Table 7.
[0078] Table 7 Changes in three-phase permeability before and after injection into the system
[0079] <![CDATA[Permeability before injection system / 10 -3 μm 2 > <![CDATA[Permeability after injection system / 10 -3 μm 2 > Blockage rate / % Gas Phase 49 2.9 94.1 oil phase 9.6 8.9 7.3 Water Phase 20.4 8.1 62.3
[0080] The present invention has been disclosed in the above preferred embodiments, but those skilled in the art should understand that these embodiments are only used to describe the present invention and should not be construed as limiting the scope of the present invention. Further improvements can be made without departing from the principles of the present invention, and these improvements should also be regarded as protections of the present invention.
Claims
1. A nanofluid system for selectively blocking gas channeling, characterized in that: The raw material composition is calculated according to mass fraction as follows: Modified nanoparticles: 30% to 32%, Activator: 20-22%, Dispersant: 0.1%~0.2%, Clay stabilizer: 0.1% to 0.2%, The rest is water; The sum of the above components is 100%; The modified nanoparticles are one of nano SiO2 particles and nano TiO2 particles whose surfaces are modified by a silane coupling agent; the clay stabilizer is one of sodium hydroxide and potassium hydroxide; and the activator is sodium silicate.
2. The nanofluid system for selectively blocking gas channeling according to claim 1, characterized in that: In the modification process of the modified nanoparticles, the mass ratio of the nanoparticles, the solvent and the silane coupling agent is 1:(9-11):(2-5).
3. The nanofluid system for selectively blocking gas channeling according to claim 2, characterized in that: The solvent is one of toluene, ethylene glycol and ethanol.
4. The nanofluid system for selectively blocking gas channeling according to claim 2, characterized in that: The coupling agent is one of silane coupling agent KH550 and silane coupling agent KH560.
5. The nanofluid system for selectively blocking gas channeling according to claim 1, characterized in that: The dispersant is one of sodium dodecylbenzenesulfonate, hexadecyltrimethylammonium bromide and Triton X-100.
6. A method for preparing a nanofluid system for selectively blocking gas channeling, used for preparing the nanofluid system for selectively blocking gas channeling according to any one of claims 2 to 5, characterized in that: The steps include: (1) drying the nanoparticles to obtain pretreated activated nanoparticles; adding the pretreated activated nanoparticles and a silane coupling agent to a solvent under stirring conditions, stirring and reacting at 75 to 90° C., filtering, and drying to obtain modified nanoparticles; (2) gradually adding the modified nanoparticles into fresh water under stirring conditions to obtain a modified nanoparticle suspension; (3) adding a dispersant and a clay stabilizer to the modified nanoparticle suspension prepared in step (2) in sequence, so that the pH of the solution is maintained at 10 to 11, and stirring evenly to obtain a nanoparticle water-based solution system having a viscosity equivalent to that of water; (4) adding an activator to the nanoparticle water-based solution system formed in step (3) under stirring conditions to form a nanofluid system.
7. An application of a nanofluid system for selectively blocking gas channeling, characterized in that: The nanofluid system for selectively plugging gas channel as described in any one of claims 1-6 is injected into the formation, and the gas containing CO2 is added to the formation so that CO2 passes through the nanofluid system and is dehydrated to form a glassy solid substance, thereby reducing the gas phase permeability and plugging the gas production channel.
Citation Information
Patent Citations
Method for controlling steam channeling of steam-injected oil reservoir
CN104314540A
Non-acid solution high-strength plugging agent, and preparation method thereof
CN105602536A